PHRASEOLOGY AND PHRASES ABOUT FAMILY IN USE IN ENGLISH LANGUAGE - Solijonova , Mahbuba Bo‘riboy qizi (Educational Research in Universal Sciences, 2023)
Through this article, the comparative study of the phrases in the languages with each other shows that it is necessary to focus on essential aspects such as the traditions and cultures of the nation through the smallest unit of the society “family” and the expressions related to it. In the process of learning any language, it is possible to realize the inner world of that nation. Some phrases are exist that the meaning of it can only be translated or understood as long as person has a clear understanding of the customs, culture or the history of that nation, thus thoughts and views are given that phraseology in terms of family is directly related to them.